Bound States in the Continuum in All‐Dielectric Metasurface: Separation of Sub‐10 nm Enantiomers. Issue 3 (22nd December 2021) - Mao, Libang; Liu, Kuan; Lian, Meng; Jia, Jingyuan; Su, Ying; Ren, Haonan; Zhou, Lei-Ming; Cao, Tun
Abstract : Enantioseparation is crucial in pharmaceutics and agrochemicals. Compared to the current chemical technique, the optical enantioseparation is more effective means yet hampered by the weak chiral optical force. Recently, plasmonic nanostructures have been theoretically demonstrated to excite superchiral fields that can enhance enantioselective optical forces. Yet, the quality ( Q ) factors of plasmonic resonances are limited by the ohmic losses intrinsically existing in metals, thus hindering their applications for sorting of a few nanometer size chiral molecules (i.e., proteins and DNA). Herein, a dielectric metasurface consisting of an array of silicon (Si) rings with a broken symmetry is proposed. This dielectric metasurface can excite a sharp high‐ Q magnetic dipolar (MD) resonance caused by a distortion of symmetry‐protected bound states in the continuum (BICs), so called quasi‐BIC. It is shown that this quasi‐BIC MD resonance can pronouncedly improve the chiral lateral force on the paired enantiomers under linearly polarized illumination, offering an enantioseparation of sub‐10 nm nanoparticles with chirality parameters of ±0.2 in 1 ms. The work provides a new approach for enantiopurification and enantioseparation, taking a novel perspective to discriminate and separate chiral molecules in the chemical and pharmaceutical industries. Abstract : Quasi‐bound state in the continuum (BIC)‐induced resonance is theoretically demonstrated in all‐dielectric metasurface consisting of asymmetric Si microrings array. Such a resonance can significantly enhance the chiral field to separate the paired sub‐10 nm enantiomers under linearly polarized illumination.